Present bias and externalities: Can government intervention raise welfare? - Christos Kotsogiannis; Robert Schwager (Canadian Journal of Economics/Revue canadienne d'économique, 2022)
Quasi-hyperbolic discounted preferences imply that consumers overemphasize immediate current rewards and overlook future ones (they have a “bias for the present”). Within this context the literature has emphasized that the misalignment between immediate and future rewards can be rectified by government policy. Importantly, it has also been shown that intervention by a government that shares the same biased intertemporal preferences with consumers does not deliver welfare improvements. Focusing on the latter, this paper identifies conditions under which, in the presence of quasi-hyperbolic preferences and a market imperfection (which takes the form of a negative externality), intervention by a present-biased government is welfare enhancing. This is the case if the market imperfection is sufficiently strong or the consumers' bias for the present is weak.
Keywords: 330